Bob Dylan all the songs : the story behind every track - Margotin, Philippe; Guesdon, Jean-Michel (Black Dog & Leventhal, 2015)
A comprehensive account of Bob Dylan's album cuts, bootlegs, and soundtrack recordings includes details that led to the composition of each song, what went on in the recording studio, and behind-the-scenes accounts of musicians on each track